Practitioners' validation on effectiveness of multimedia Mobile Learning Application for children - Ibrahim, N. (Institute of Electrical and Electronics Engineers Inc., 2016)
Mobile Learning Application (MLA) is one of mobile learning (m-learning) categories where many studies highlighted the strengths and advantages of MLA include sharing of teaching and learning materials, learners can perform educational works according to their own affordance and teaching and learning activities can be conducted at any time and any place. MobChild conceptual model is developed for the implementation of MFolktales mobile application. This paper presents the practitioners' perceptions on the effectiveness of MobChild conceptual model. Eight (8) variables have been identified through background identification and integration of theoretical solutions. The variables are mobile apps technology, layout, content, navigation, touch gestures, learning theory, scaffolding and user. Descriptive analysis and relationship evaluation have been conducted to validate the effectiveness of the variables that included in the model. Pearson's product-moment correlation has been conducted to determine significant correlation between each variable. The results from the test show that the Pearson's product-moment correlation for all relationships displayed strong positive correlations. Thus, there were statistically proven that mobile apps technology, layout, content, navigation, touch gestures, learning theory, scaffolding and user variables should be applied in the development of MFolktales mobile application. Â© 2016 IEEE.